Evidence of Residual Ongoing Viral Replication in Chronic Hepatitis B Patients Successfully Treated With Nucleos(t)ide Analogues. (22nd December 2022) - Yu, Tong; Zhang, Miaoqu; Zhang, Hanyue; Zheng, Jianming; Shen, Chuan; Jiang, Ning; Zou, Lei; Wang, Jing; Yu, Yiqi; Zhang, Qiran; Yu, Shuili; Huang, Yanfang; et al.
Abstract: Background: Chronic hepatitis B is usually treated with nucleos(t)ide analogues (NAs). However, a cure is rarely achieved, even with years of treatment. Here, we investigated whether viral replication is completely halted and how long covalently closed circular DNA (cccDNA) persists in patients successfully treated with NAs. Methods: A series of longitudinal serum samples and a collection of cross-sectional liver biopsies were obtained from patients successfully treated with NAs. Viral variants in serum HBV RNA were enumerated by deep sequencing. Viral replication intermediates in hepatocytes were directly visualized by in situ hybridization. The apparent half-life of each cccDNA was estimated. Results: Three of 6 successfully treated patients demonstrated clear evidence of a small proportion of virus evolution, although the overwhelming proportion of variants were identical or possessed a similar degree of divergence through time. The apparent half-life of variants was estimated to be from approximately 7.42 weeks to infinite. Hepatocytes remained positive for cytoplasmic nucleocapsids-associated relaxed circular DNA in 4 of 7 liver needle biopsies. Conclusions: We conclude that even after prolonged treatment, a small proportion of the cccDNA reservoir is constantly replenished by continued low-level HBV replication, whereas a large proportion of the cccDNA reservoir persists over time. Abstract : Our findings provide evidence that residual ongoing HBV replication exists in chronic hepatitis B patients successfully treated with nucleos(t)ide analogues. Given the estimated half-life of cccDNA, it may require many years or even life-long treatment to effectively eliminate HBV.